HIKMAH LARANGAN NIKAH MUT’AH (KAWIN KONTRAK) PERSPEKTIF HUKUM ISLAM: THE WISDOM OF THE PROHIBITION OF MUT'AH MARRIAGE (CONTRACT MARRIAGE) PERSPECTIVE OF ISLAMIC LAW - Hermawati, Yuli; Malik, Muhammad Abdul (Mitsaqan Ghalizan, 2022)
This journal article discusses mut'ah marriage or often called contract marriage which aims to explain and discuss mut'ah marriage from an Islamic perspective and the law of mut'ah marriage. This research is motivated by the large number of people who enter into contract marriages which are very detrimental to the woman. The purpose of this research is that I, as the writer and the readers, are able to understand and know more about mutah marriage so that no one else does it because apart from being prohibited in Islam, mutah marriage is very detrimental to themselves as well as to both parties and their offspring. This research is also conducted so that we can be more motivated in implementing and studying other Islamic laws as well. The method used in this study is the library research method. Every religion has laws and rules that should be used as examples and guidelines in the life of Mut'ah marriage. The law is Haram, which has been explained in the Al-Quran and Hadith. Readers are also able to do something rationally